Current clinical management of constitutional delay of growth and puberty - Rossella Gaudino; Gianpaolo De Filippo; Elena Bozzola; Manuela Gasparri; Mauro Bozzola; Alberto Villani; Giorgio Radetti (BMC, 2022)
Abstract Background Constitutional delay of growth and puberty (CDGP) is classified as the most frequent cause of delayed puberty (DP). Finding out the etiology of DP during first evaluation may be a challenge. In details, pediatricians often cannot differentiate CDGP from permanent hypogonadotropic hypogonadism (PHH), with definitive diagnosis of PHH awaiting lack of puberty by age 18 yr. Neverthless, the ability in providing a precise and tempestive diagnosis has important clinical consequences. Main text A growth failure in adolescents with CDGP may occur until the onset of puberty; after that the growth rate increases with rapidity. Bone age is typically delayed. CDGP is generally a diagnosis of exclusion. Nevertheless, other causes of DP must be evaluated. A family history including timing of puberty in the mother and in the father as well as physical examination may givee information on the cause of DP. Patients with transient delay in hypothalamic-pituitary-gonadal axis maturation due to associated conditions, such as celiac disease, inflammatory bowel diseases, kidney insufficiency and anorexia nervosa, may experience a functional hypogonadotropic hypogonadism. PHH revealing testosterone or estradiol low serum values and reduced FSH and LH levels may be connected to abnormalities in the central nervous system. So, magnetic resonance imaging is required in order to exclude either morphological alterations or neoplasia. If the adolescent with CDGP meets psychological difficulties, treatment is recommended. Conclusion Even if CDGP is considered a variant of normal growth rather than a disease, short stature and retarded sexual development may led to psychological problems, sometimes associated to a poor academic performance. A prompt and precise diagnosis has an important clinical outcome. Aim of this mini-review is throwing light on management of patients with CDGP, emphasizing the adolescent diagnosis and trying to answer all questions from paediatricians.